SAFETYGUIDE: DIGITAL TRANSFORMATION OF OPERATIONAL SAFETY IN ELECTRICAL SYSTEMS THROUGH AUGMENTED REALITY - Silva, Stony; Caetano Vilela Dias de Souza; Diego Andrade Faura; William Aparecido Celestino Lopes; Marcelino Siqueira de Carvalho (Revista e-TECH: Tecnologias para Competitividade Industrial - ISSN - 1983-1838, 2025)
This study investigates the application of Augmented Reality (AR) for optimizing operational safety in the maintenance of electrical systems, focusing on the digitization and standardization of hazardous energy lockout procedures. Using the Design Science Research (DSR) methodology, which guides the structure and development of projects and is essential for artifact creation, providing a structured and problem-solving-focused approach, the SafetyGuide application was developed. This app, integrated with AR, automates and standardizes the processes for electrical energy lockout. The effectiveness of the solution was tested in the metallurgy industry using risk scenario simulations. Validation of the SafetyGuide application with 11 employees revealed positive acceptance, with most users rating its intuitiveness, accuracy, and usability above 9 on a scale of 0 to 10. The application was considered effective in guiding users through the lockout procedure, with 90% of participants affirming that the tool was useful for the safety process. The results indicate that the integration of AR and digitization can significantly transform safety protocols in electrical maintenance, aligning with the requirements of Industry 4.0. SafetyGuide represents an innovation in industrial safety, with potential applications across various industries, offering a model for future research on implementing advanced technologies in safety practices. .